2015
DOI: 10.1177/1742715015577889
|View full text |Cite
|
Sign up to set email alerts
|

Some announcements, reaffirming the critical ethos of Leadership, and what we look for in submissions

Abstract: This editorial begins with a number of announcements and then considers how the journal and the community of scholars who edit it, write for it, review for it and read it can continue to collectively move it forward. I hope this gives contributors a clearer idea of the journal's orientation, and in doing so offers some useful insights into how authors might improve their chances of a paper being published in Leadership.We start with news of an editorial transition. Brad Jackson, my co-editor for over the past … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
35
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 32 publications
(39 citation statements)
references
References 21 publications
2
35
0
Order By: Relevance
“…In particular, that journal ranking systems are contributing to pressure to publish and publication anxiety (Tijdink et al, 2013) and that most academics surveyed feel they have insufficient time to undertake their research (Kinman & Jones, 2003). Further, the findings also provide empirical support for the assertion that ranking systems have inhibiting effects on innovative, risky research and encourage safe, conforming mainstream orthodoxy (Alvesson & Sandberg, 2013;Lincoln, 2012;Macdonald & Kam, 2007;Ozbilgin, 2009;Powell & Woerndl, 2008;Tourish, 2015;van Dalen & Henkens, 2012). The findings also support allegations in the literature that regional, cross-disciplinary (McNay, 1998;Rafols, Leydesdorff, O'Hare, Nightingale, & Stirling, 2012) and qualitative research is threatened (Lincoln 2012, Chen andHirschheim 2004).…”
Section: Discussion On Findingssupporting
confidence: 53%
See 4 more Smart Citations
“…In particular, that journal ranking systems are contributing to pressure to publish and publication anxiety (Tijdink et al, 2013) and that most academics surveyed feel they have insufficient time to undertake their research (Kinman & Jones, 2003). Further, the findings also provide empirical support for the assertion that ranking systems have inhibiting effects on innovative, risky research and encourage safe, conforming mainstream orthodoxy (Alvesson & Sandberg, 2013;Lincoln, 2012;Macdonald & Kam, 2007;Ozbilgin, 2009;Powell & Woerndl, 2008;Tourish, 2015;van Dalen & Henkens, 2012). The findings also support allegations in the literature that regional, cross-disciplinary (McNay, 1998;Rafols, Leydesdorff, O'Hare, Nightingale, & Stirling, 2012) and qualitative research is threatened (Lincoln 2012, Chen andHirschheim 2004).…”
Section: Discussion On Findingssupporting
confidence: 53%
“…IS has been accused of having a North American bias (Gallivan & Benbunan-Fich, 2007) and that North American authors predominate in the top journals (Truex, Cuellar, & Takeda, 2009, Keller & Coulthard, 2013. Indeed, Tourish (2015) has identified that 31 out of the top 33 journals in the rankings produced by the Association of Business Schools in the UK were of US origin. Research in information systems is highly contextual.…”
Section: The Potential Effects Of Ranking On Disciplinary Researchmentioning
confidence: 99%
See 3 more Smart Citations